Optimalisasi Personal Branding dan Pemasaran Digital Untuk Meningkatkan Persaingan Di Era Ekonomi Digital Bagi UMKM - Anggi Arista (Indo Publishing, 2026)
The educational and mentoring program was conducted for one week, from January 19, 2026, to January 24, 2026. The goal of this Community Service program was to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) to manage and develop their businesses sustainably through strengthening personal branding and implementing digital marketing strategies. Specifically, this program aimed to empower MSMEs to understand the concept of personal branding, build a strong and consistent business identity, and optimize the use of digital media as a marketing tool. With targeted education and mentoring, it is hoped that MSMEs can increase product competitiveness, expand market reach, and adapt effectively to developments in the digital economy. The MSME capacity-building program through education and mentoring has proven to be instrumental in increasing business competitiveness in the digital economy era. Education on personal branding helps MSMEs build a stronger, more consistent, and more recognizable business identity for consumers. Meanwhile, implementing digital marketing strategies enables MSMEs to reach a wider market, increase customer interaction, and sustainably improve sales performance. Structured and applied mentoring has a positive impact on improving digital literacy, promotional creativity, and increasing the confidence of MSMEs in utilizing digital platforms. Thus, optimizing personal branding and digital marketing is not only a promotional tool but also a key strategy for strengthening MSMEs' position amidst increasingly competitive business conditions